Modelling and calibration of a five link elastic boom of a mobile concrete pump. Issue 1 (31st December 2023) - Meiringer, M.; Kugi, A.; Kemmetmüller, W.
ABSTRACT: Large-scale manipulators, such as the boom of a mobile concrete pump, typically rely on lightweight construction to maximize their operational range. As a result, significant elastic deformations occur during operation. Various automation and control applications require computationally fast and accurate mathematical models of the manipulator's motion. In this work, a mathematical model for the boom of a mobile concrete pump with 5 individual joints is presented. This model takes into account the elastic bending in two directions and the torsion of the boom. To reach a high model accuracy, calibration is required. This is challenging due to the large dimension and the outdoor operation, which makes the accurate measurement of the boom position difficult. A camera-based measurement setup is proposed in this work that is tailored for the considered problem. It is shown by measurements that the model is able to achieve a high accuracy with rather small computational costs.